Can Tics be Performed Convincingly by an Actor? - Kirsten R. Müller-Vahl; Laura Riemann; Hermann Krämer; Alexander Münchau (Behavioural Neurology)
Background. In the German movie “Vincent will Meer” a healthy actor portrays a man with Tourette’s syndrome. Objective. The aim of this study was to investigate whether the performance of tics is convincing and whether this judgment depends on whether he/she suffers from tics or not. Methods. While the movie was broadcasted in German cinemas, we put an online survey (including 28 questions on different aspects related to the observation, performance, and authenticity of tics) on the web pages of the German self-help group. 276/296 surveys submitted could be used for further analyses. Results. 95.7% of all participants felt that the performance of tics was convincing. However, people with tics (n=26) were less convinced compared to those who had never met a person with tics (n=110) (P=0.020). Conclusions. Our results further support the hypothesis that tics are not “abnormal” but “physiological” movements that are only misplaced both in time and context.